Myositis Ossificans Traumatica of the Wrist in Elderly: A Description of an Unusual Case - Suvarn Gupta, Pratik Kawde, Aashay Kekatpure, Sonal Karmore, Romil Rathi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Myositis ossificans commonly involves muscles and subcutaneous tissues in people of younger age group.The myositis ossificans is commonly seen around the muscles of elbow joint but occurs less commonly inmuscles around hands and wrist. We report a case of Myositis ossificans involving the wrist in a 65 year oldlady.